Developing Micro Small and Medium Enterprises (MSMEs) In The Field Of Ornamental Fish Cultivation In The Village Of Pinang Freely E-Commerce - Aris Aris; Adi Prananto; Swatantra Adikara (Universitas Raharja, 2022)
Micro, Small and Medium Enterprises (MSME) in Pinang Village currently play a major role in driving the economy of the community. This is due to the rapid growth of MSME in ornamental fish cultivation so that it has a positive impact on society. Currently, the marketing is limited. Even though it has used social media, the development of MSME in Pinang Village is very slow. To facilitate management, a forum in the form of online media in the e-commerce system has been created as a forum for the Pinang community to develop their MSME. So that they can maintain their existence and Continuous development. The research method in system analysis used for this research is PIECES which consists of Performance, Information, Economy, Control, Efficiency and Service. The system design uses object-oriented analysis methods with Unified Modeling Language (UML), the programming language used is PHP. In this research, a system will be developed whose implementation has features such as user, purchase transaction, fish categories, fish species, transaction reports. With the existence of this ecommerce system to help the development of MSME in the field of ornamental fish cultivation in Pinang Village